Memposisikan Teori dan Konsep Dasar dalam Riset Kualitatif - Zamili, Moh. (Program Pascasarjana Universitas Ibrahimy, 2016)
Theory without concepts is blind. Concept without idea is empty. Ideas lead a researcher to finding some phenomenon. Certaintly, phenomenon isn’t come partial or seperated. Every act, habit, mindset, and human behavior in everyday activity rise up categorization. The task of researcher to find out that categorization. Behind that situation and absolutely when we involve with participant, sometimes we can’t avoid from our contruct of ideas or concept. But, sometimes between real context and research perspectives comes differing. So, the important thing is how our theory can describe phenomenon and has clarity of definition or clarity in matter of terminology.